Revitalisasi pembungkus tambul (Penganan tradisional) ramah lingkungan di Kuantan Singingi - Zulfan Saam; Thamrin Thamrin; Nofrizal Nofrizal; Tengku Nurhidayah (CANANG: Jurnal Pengabdian Masyarakat, 2021)
Recently, there has been a phenomenon of changing the packaging from banana leaves to clear plastic, including for cake wrappers. The use of leaves as a wrapper does not produce waste and the food that is wrapped is not exposed to chemicals. Therefore, it is necessary to socialize the dangers of plastic wrapping for human health. The purpose of this service activity is to increase public understanding and knowledge about the use of plastics and dyes in food, to re-promote the manufacture and consumption of tambul or traditional, environmentally friendly snacks.This service is carried out by using (1) the method used to convey the main points of material relating to plastic wrapping and its dangers to health, leaf wrapping and its benefits for health. (2) practice, making: pulut kucung, lopek luwo and guwajik. The target groups for this service are village officials, mothers and adolescents in Kampung Baru Sentajo, which connects 30 people. The result of this service is to increase public knowledge about the dangers of using plastics and dyes in food. In addition, the local community will reactivate the tambul wrapping using banana leaves. The packaging is an environmentally friendly material, so the food consumed is healthy food and is the local wisdom of the Kuantan Singingi people.